The Exposure of Gap Competence causes in Stunting Children Ages 0-12 Months in Makassar Indonesia: Cross-Sectional Study - Mustamin1 , Sirajuddin2 , Mahmud3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction, The parenting gap is believed to be one of the variables that influence stunting. The Objectivesof this study to identify gaps in care (feeding practices, care, hygiene, and treatment of children) andincidence of stunting. Method this study is a cross-sectional, conducted in March-June 2020 in Makassar CityIndonesia. The sample size was 82 people, of children aged 0-12 months. The data collectors are alumni ofapplied nutrition and dietetics degrees, trained for 2 days in health protocol, interviews, and anthropometry.The instrument in this study was developed from the UNICEF. The result, found that mothers and fathersgraduated from high school, 43% and 59.8%, respectively. The work of mothers as housewives is 84.1% andfathers are private employees as much as 36.6%. The parenting competency gap in the feeding practice ofchildren aged 0-6 months, 7-9 months, and 10-12 months is 20.9%, 71.79%, and 92.31%, respectively. Theresults of statistical analysis showed that there was an effect of parenting competency gaps on stunting (p= 0.000). The conclusion is that the parenting competency gap is proven to affect the incidence of stunting.The suggestion is that it is necessary to increase the capacity of mothers in child care practices/